An update on the occurrence of Paracoccidioides species in the Midwest region, Brazil: Molecular epidemiology, clinical aspects and serological profile of patients from Mato Grosso do Sul State. - Karine Mattos; Tiago Alexandre Cocio; Edilânia Gomes Araújo Chaves; Clayton Luiz Borges; James Venturini; Lídia Raquel de Carvalho; Rinaldo Poncio Mendes; Anamaria Mello Miranda Paniago; Simone Schneider Weber (Public Library of Science (PLoS), 2021)
Background Paracoccidioidomycosis (PCM) is a systemic and endemic fungal infection in Latin American, mainly in Brazil. The majority of PCM cases occur in large areas in Brazil, comprising the South, Southeast and Midwest regions, with the latter demonstrating a higher incidence of the species Paracoccidioides lutzii. Methodology and main findings This study presents clinical, molecular and serological data of thirteen new PCM cases during 2016 to 2019 from the state of Mato Grosso do Sul, located in the Midwest region, Brazil. From these thirteen cases, sixteen clinical isolates were obtained and their genomic DNAs were subjected to genotyping by tub1 -PCR-RFLP. Results showed Paracoccidioides brasiliensis sensu stricto (S1) (11/16; 68.8%), Paracoccidioides restrepiensis (PS3) (4/16; 25.0%) and P. lutzii (1/16; 6.2%) as Paracoccidiodes species. Therefore, in order to understand whether the type of phylogenetic species that are circulating in the state influence the reactivity profile of serological tests, we performed double agar gel immunodiffusion (DID), using exoantigens from genotyped strains found in this series of PCM cases. Overall, our DID tests have been false negative in about 30% of confirmed PCM cases. All patients were male, most with current or previous rural activity, with ages ranging from 17 to 59 years, with 11 patients (84.6%) over 40 years of age. No clinical or epidemiological differences were found between Paracoccidioides species. However, it is important to note that the only case of P. lutzii died as an outcome. Conclusions This study suggests P. brasiliensis sensu stricto (S1) as the predominant species, showing its wide geographic distribution in Brazil. Furthermore, our findings revealed, for the first time, the occurrence of P. restrepiensis (PS3) in the state of Mato Grosso do Sul, Brazil. Despite our setbacks, it would be interesting to provide the complete sequencing of these clinical isolates to complement the molecular information presented.